Pengaruh Religiusitas Dan Pengetahuan Konsumen Terhadap Keputusan Pembelian Properti Pada PT.Griya Permata Kencana Jambi - Lady Ragia Alfa; A. Tarmizi; Agustina Mutia; Victor Diwantara (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2024)
The demand for houses is increasing from year to year in line with the growth in population in Indonesia. Meanwhile, the availability of houses is not proportional to the large number of requests. This is one of the factors causing the very high increase in house prices. In the city of Jambi, there are already several houses that use the conventional system, namely using interest in their operational transactions, such as KPR Bank BRI, Bank Mandiri, Bank BNI and others. Meanwhile, housing developments that use the sharia system have increased. The middle-urban community who are critical and want to implement an Islamic lifestyle one hundred percent are starting to switch, they are no longer using conventional and sharia mortgages that are sold in national banks, but instead are utilizing sharia-based mortgage facilities in sharia housing, which are not products of banking financial institutions, but from developers. This study aims to determine the effect of religiosity and consumer knowledge on purchasing decisions of sharia property at PT. Griya Permata Kencana Jambi. The subjects of this research are consumers of PT. Griya Permata Kencana Jambi. The population in this study amounted to 220 people and a sample of 69 people. And the research method used is quantitative method, this study uses primary and secondary data with multiple linear regression models.